An adaptive meshless method based on friction condition control strategy. (December 2019) - Sun, Yuantao; Zhai, Jinjin; Zhang, Qing; Qin, Xianrong
Abstract: The friction in plastic forming has a great influence on metal plastic forming. As friction can increase the forming resistance and further lead to insufficient plastic forming of objects, it will result in poor forming quality or even failure. To solve these problems, the numerical simulation method is used to guide the forming process. However, because of the shear friction and the unsuitable mesh the contact pressure oscillation in the finite element method often results in the decrease of the accuracy and interrupt of the calculation. In this paper an adaptive meshless method based on friction control is proposed: firstly the rates of the pressure change and the strain energy gradient in the model are carried out, then according to them the nodes are automatically densified on the basis of the node refinement strategy. The method can solve the pressure oscillation problem and increase the accuracy, so that the forming quality can be obviously improved. Finally, an numerical example of upsetting process is given to verify the effectiveness of the adaptive meshless method and its function in failure analysis. Highlights: Using adaptive EFGM to analyze friction in plastic forming process According to the gradient of strain energy and node refinement strategy to confirm where nodes should be densified Applying adaptive EFGM to study friction force in upsetting for demonstrating its effectiveness in failure analysis